Effect of Cone-beam computed tomography (CBCT) Outside the Field of View among Emergency Physicians and health care working in X-Ray department in Public Sector Tertiary Hospitals at Saudi Arabia 2022 - Sultan Mathkar Nawar Althiyabi , Talal Mathkar Nawar Althiyabi , Hesham Ali Alshehri , Muteb Mansour Alkalawi , Ahmed Theyab Almutairi , Yasser Ghazai alotaibi; Mohammed Abdulrahman Ghali Alotaibi , Nayef Muhammad Al-Dajani , Omar yousef alserihy , Abdulaziz Mubarak Barak Al-Otaibi , Adnan Barkat Alsowihri , Metib Ziad Nafel AL-juaid (Migration Letters, 2022)
Background: Cone-beam computed tomography (CBCT) is widely used in practice among Emergency Physicians and health care working . It became an essential tool for implant and surgical planning . However, the main limitation of CBCT is presence of artifacts. Images artifacts are distortion of recorded data on CBCT image. It occurs due to the interactions between x ray beam and high-density dental materials with high atomic number causing beam hardening . Several studies reported that presence of dental implants, metallic fillings, crowns, and root canal fillings in the field of view (FOV) could inversely affect the image quality due artifacts production and subsequently impair the final diagnosis. Moreover, there is another source of artifacts which is called exomass-related artifacts. The structures present outside the FOV, but at the same axial plane between the tube and the image receptor . These artifacts have variable appearance within the CBCT images; discrete stripe-like, ring-like patterns, double contours, and overall lack of sharpness. It is reported that exomass artefacts increase the mean voxel density values and noise of CBCT images . Aim of the study: To effect of Cone-beam computed tomography (CBCT) Outside the Field of View among Emergency Physicians and health care working in X-Ray department in Public Sector Tertiary Hospitals at Saudi Arabia 2022. Methods: This cross-sectional study was conducted among 300 participants from Public Sector Tertiary Hospitals kingdom of Saudi Arabia. A validated self-administered questionnaire was used, emergency Physicians and health care working in X-Ray, Computed Tomography, and Magnetic Resonance Imaging department It includes questions on socio demographic variables, during the August to September 2022. Results: show the remaining socio-demographic characteristics of the participant regarding age most of participants 40-50 years were (33.0%) the gender majority of participants were(59.0%) were the marital status the most of participant were (52.0%) married while single were (27.0%) , regarding the department the most of participant radiology were (44.0%). Conclusion: In conclusions, the variability of voxel density value and hypo dense artifacts of CBCT images due to high density objects outside the FOV is well documented in several studies. The effect of FOV, voxel size, kVp and mill amperage on these artifacts has been evaluated.